Evaluating plasma lactate running speed derived parameters for predicting maximal lactate steady state in teaching horses - Littiere, T. O. [UNESP]; Costa, G. B. [UNESP]; Sales, N. A.A. [UNESP]; Carvalho, J. R.G. [UNESP]; Rodriguez, I. D.M. [UNESP]; Ramos, G. V. [UNESP]; Ferraz, G. C. [UNESP] (Elsevier, 2025)
In humans, there is an ongoing academic discussion about measuring plasma lactate concentration ([La−]) during an incremental exercise test (IET) to establish thresholds that can predict the maximal lactate steady state (MLSS). Training studies on horses have utilized the onset of [La−] (OBLA4 mM), also known as V4, the velocity at which the [La−] of 4 mM is reached. This study assesses the effectiveness of four methods for estimating the MLSS in teaching horses. Ten teaching horses underwent a single IET to determine four exercise intensity thresholds for predicting MLSS and performed several constant intensity running bouts to obtain the MLSS. The velocity corresponding to the visual lactate threshold (VLTV) reached by the horses during IET was the intensity in the first bout. A randomized and blind trial used a visual analysis (LTV) and a bi-segmented linear regression model (LTBI). The agreement among the velocities corresponding to the V2, V4, VLTV, and VLTBI and the MLSS (VMLSS) was established using mean difference (MD), ordinary least products (OLP), and correlation coefficient (r). The average plasma [La−] at MLSS was 1.50 ± 0.37 mM, and the V4 was higher than VMLSS with an MD of 2.12 ± 0.59 m/s between them. V2 and VLTV showed the lowest mean bias when compared to the VMLSS. The V4 threshold, as determined with the IET protocol used, is unsuitable for estimating MLSS. In the exercise test protocol used in this study, predicting the VMLSS based on V2, VLTV, or VLTBI may be more accurate.
Keywords: Anaerobic threshold; Exercise; Exercise intensity domains; Fatigue; Physiological markers